Identification of Alternations in the Structure of Historical Masonry Walls Using the GPR Method Accompanied with Architectural Survey in the Former Piast Gymnasium in Brzeg - Frąckiewicz, Piotr; Raszczuk, Krzysztof; Jasieńko, Jerzy (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Widely used in civil engineering, GPR (ground penetrating radar) is increasingly being used to survey historic structures. However, there are still no conclusive directives on the use of GPR in the identification and diagnosis of masonry structures. The current state of the art allows only on the example of individual case studies, to draw conclusions about the effectiveness of the use of this tool.
Keywords: ground penetrating radar; non-destructive testing; NDT; masonry structures; GPR